Regulating financial conglomerates - Freixas, Xavier; Lóránth, Gyöngyi; Morrison, Alan D. (Journal of Financial Intermediation, 2007)
We analyze the risk-taking incentives of a financial conglomerate that combines a bank and a non-bank financial intermediary. The conglomerate's risk-taking incentives depend on the level of market discipline it faces, which in turn is determined by the conglomerate's liability structure. We examine optimal capital regulation for standalone institutions, for integrated conglomerates and holding company conglomerates. We show that, when capital requirements are set optimally, capital arbitrage within holding company conglomerates can raise welfare by increasing market discipline. Because they have a single balance sheet, integrated conglomerates extend the reach of the deposit insurance safety net to their non-bank divisions. We show that the extra risk-taking that this effect causes may wipe out the diversification benefits within integrated conglomerates. We discuss the policy implications of these results.